PENGENALAN ANALISIS SENTIMEN BAGI SISWA AS-SAKINAH FONDATION BAMBU APUS PAMULANG TANGERANG SELATAN. : PENGENALAN ANALISIS SENTIMEN BAGI SISWA AS-SAKINAH FONDATION BAMBU APUS PAMULANG TANGERANG SELATAN. - Adam Muiz; Raditia Vindua; Nurhayati (Abdi Jurnal Publikasi, 2024)
Introduction To Sentiment Analysis For As-Sakinah Students Of The Bamboo Apus Pamulang Fondation, South Tangerang. This Community Service was held to provide understanding to the students of the As-Sakinna Foundation so that in order to express their emotions and opinions, there are three main types of sentiment: Emotion, Opinion, and Polarity. Apart from that, it is also important to understand that the complexity of sentiment is not just black and white, but there are many factors that influence a person's sentiment. For this reason, the Pamulang University Community Service team provides outreach regarding the basic principles of sentiment analysis. This Community Service activity is carried out using the workshop method, where the method is carried out in several forms of activities, such as lectures as well as presenting material regarding the basics of sentiment analysis using PowerPoint, Infocus, providing basic material, application in life, as well as describing technological developments related to analysis. sentiment for the future. With this method, students and teachers have more inspiration and knowledge about how to carry out sentiment analysis. This community service activity went smoothly, on time, and as expected. This was proven by the participants' active participation in the entire event process and the question and answer process regarding the material provided.